(untitled) (Nepal Journal of Epidemiology, 2021)
Background: The Hematological neoplasms (HN) are a heterogeneous group of cancers that originated in the hematopoietic or lymphoid tissues. There is reduced information published regarding HN mortality in Ecuador. This study aims to present the crude and age-specific mortality rates for HN in the Ecuadorian population. Methods: We performed a cross-sectional study through the national database of defunctions published by the Ecuadorian National Institute of Statistics and Census, 2019. We used the ICD-10 codes to classify the HN. Results: During 2019, 1462 deaths were reported, 53.83% were males, 87.96% of mestizo ethnicity, and 78.32% residents in urban areas. The median age was 62 years, with an interquartile range of 34. The crude mortality rate obtained was 8.49 per 100000 inhabitants, and the higher age-specific mortality rates was 43.29 per 100000 inhabitants aged ≥ 60 years, contrasting with the 2.63 per 100000 inhabitants in people aged < 20 years. Considering each ICD-10 group, we found the following rates by 100000 inhabitants; C85 2.04, C91 1.92, C92 1.46, C90 1.11, C83 0.70, C95 0.48, C81 0.38, C84 0.16, C82 0.10, C96 0.05, C93 0.04, C86 and C94 0.02, and C88 0.01. Conclusion: In Ecuador, during 2019, approximately eight people died due to HN by 100000 inhabitants, affecting mainly people aged ≥ 60 years. The most frequent neoplasms were Non-Hodgkin lymphomas, similar to other reports globally. These results should be analyzed considering some deficiencies in the Ecuadorian health system and the national registry. Therefore, we suggest conducting more studies regarding HN.